New approaches for revegetating agricultural landscapes to provide connectivity for wildlife: The example of the Tasmanian Midlands, Australia. (30th December 2021) - Davidson, Neil J.; Bailey, Tanya G.; Burgess, Sebastian; Potts, Brad M.
Summary: There is an ongoing search for cost‐effective, practical and successful methods for landscape‐scale restoration required to meet the challenges posed by the United Nations Decade on Restoration 2021–2013. Mechanised cultivation techniques (rip mounding and Wilco spot cultivation), a range of revegetation strategies (dense reafforestation, riparian corridors, vegetation islets and scattered tree plantings) and best horticultural practice were employed to successfully establish extensive areas of local native trees and shrubs in highly altered agricultural landscapes within the Midlands of Tasmania, Australia. This region has been intensely farmed for the last 200 years and is characterised by past failures in native tree plantings. Between 2009 and 2018, 1800 ha were revegetated with a suite of hardy local native species to enhance, buffer and connect native vegetation remnants. These techniques were applied at a landscape scale to create biodiversity corridors that crossed the Midlands. Riparian corridors 100–200 m wide were created along 21 km of riverbank at an average density of 440 stems/ha. Fenced vegetation islets and individually caged scattered trees were established within and surrounding native vegetation remnants, at an average density of 143 stems/ha. Whole paddocks were densely reafforested at up to 800 stems/ha. Despite this, re‐establishing structurally complex and species diverse native vegetation, which can provide habitat for local native animals, proved challenging. In areas highly altered by a long history of farming, repeated interventions and long‐term relationships with landholders will be needed to achieve restoration objectives.